Industrial legacy towards modern urban environment: a comparative study of Wroclaw and Brno - Kunc, Josef; Sikorski, Dominik; Novotná, Markéta; Brezdeń, Paweł; Ilnicki, Dariusz; Tonev, Petr; Marek, Aneta (Bulletin of Geography. Socio-economic Series, 2023)
The paper examines the spatial structure of industrial production in the urban environment of two Central European cities, Wroclaw and Brno, and their changes during the transformation from centrally controlled to capitalist economies. The study used mapping techniques to analyse the spatial distribution of industrial activities, focusing on the representation of industrial sectors and major industrial enterprises in both cities. The research aimed to evaluate the spatial impacts of deindustrialization on the urban environment and subsequently interpret the functional and structural changes in the cities. Standard methodological procedures in regional sciences, including descriptive statistics and ArcGIS visualization, were employed. The results revealed similarities and differences in the transformation of the two cities and indicated the substantial scale of their post-industrial transformation. Major structural changes have occurred since the 1990s. The last two decades have been directed towards creating modern post-industrial environments while retaining the significant and visible industrial heritage.